2008
DOI: 10.1094/pdis-92-5-0831a
|View full text |Cite
|
Sign up to set email alerts
|

First Report of Rhizoctonia solani on Mung Bean (Vigna radiata) Sprouts in California

Abstract: In March 2007, mung bean (Vigna radiata) sprouts produced in an indoor sprouting facility in northern California developed brown lesions beginning 5 days after germination. Dark brown-to-reddish brown lesions with distinct margins developed on the stem, hypocotyl, and first true leaves of affected sprouts. Although all seed is routinely soaked in 20,000 mg Ca(OCl)2/liter of water for 15 min before germination, approximately 5 to 10% of the bean sprouts in several growing baskets (1.5 × 1.5 m) were affected and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
1

Year Published

2010
2010
2018
2018

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 0 publications
0
2
0
1
Order By: Relevance
“…This global crop, encounters a number of operational constraints, including pests and diseases that limit its production and yield potentials from seedling to harvest and often provoking grain yield loss of over 35 per cent (Asiwe, 2006). Brien et al, (2008) identified Rhizoctonia solani (Kuhn) on the basis of morphological features as causal pathogen on mungbean. R. solani is known to affect many crops.…”
Section: Issn: 2319-7706 Volume 7 Number 09 (2018)mentioning
confidence: 99%
“…This global crop, encounters a number of operational constraints, including pests and diseases that limit its production and yield potentials from seedling to harvest and often provoking grain yield loss of over 35 per cent (Asiwe, 2006). Brien et al, (2008) identified Rhizoctonia solani (Kuhn) on the basis of morphological features as causal pathogen on mungbean. R. solani is known to affect many crops.…”
Section: Issn: 2319-7706 Volume 7 Number 09 (2018)mentioning
confidence: 99%
“…The binucleate isolates were characterized as AG F (18%) and AG A (2%). Rhizoctonia solani AG 4 and AG 2‐2 isolates have been reported before on common bean (Bolkan and Ribeiro, 1985; Nelson et al., 1996; Fenille et al., 2002; Balali and Kowsari, 2004; Chang et al., 2005; O’Brien et al., 2008). Binucleate Rhizoctonia isolates have been studied less, but AG F and AG A have also been reported before on bean (Eken and Demirci, 2004; Yang et al., 2005).…”
Section: Discussionmentioning
confidence: 87%
“…S. rolfsii sulit dikendalikan karena patogen mampu mempertahankan dirinya pada tanah dalam bentuk struktur istirahat pada kondisi tanah yang ekstrim dan mampu bertahan selama lebih dari 10 tahun. Cendawan S. rolfsii tercatat mempunyai kisaran inang yang luas, terutama menyerang tanaman muda seperti pada tanaman kedelai (O'Brein et al, 2008). Perkembangan dan penyebaran inokulum penyakit dilapangan sangat dipengaruhi oleh faktor abiotik seperti suhu, kelembaban dan termasuk keadaan tanah.…”
Section: Pendahuluanunclassified